2019
DOI: 10.1083/jcb.201812122
|View full text |Cite
|
Sign up to set email alerts
|

SGK phosphorylates Cdc25 and Myt1 to trigger cyclin B–Cdk1 activation at the meiotic G2/M transition

Abstract: The kinase cyclin B–Cdk1 complex is a master regulator of M-phase in both mitosis and meiosis. At the G2/M transition, cyclin B–Cdk1 activation is initiated by a trigger that reverses the balance of activities between Cdc25 and Wee1/Myt1 and is further accelerated by autoregulatory loops. In somatic cell mitosis, this trigger was recently proposed to be the cyclin A–Cdk1/Plk1 axis. However, in the oocyte meiotic G2/M transition, in which hormonal stimuli induce cyclin B–Cdk1 activation, cyclin A–Cdk1 is noness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 68 publications
4
32
0
Order By: Relevance
“…On the other hand, translation of Sgk1 mRNA was significantly decreased in AF oocytes (Figures 1b and 3b), we decided to supress SGK1 protein kinase activity in YF oocytes using the specific SGK1 inhibitor (GSK‐650394; 10 µM). SGK1 affects CDK1 activity (Hiraoka, Hosoda, Chiba, & Kishimoto, 2019), thus we validated successful SGK1 inhibition via decrease of CDK1 (Thr161) phosphorylation in YF oocytes (3 h post IBMX removal in the presence of the inhibitor) (Figure ). Subsequently, we assayed meiotic progression of YF oocytes treated with vehicle or SGK1 inhibitor.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…On the other hand, translation of Sgk1 mRNA was significantly decreased in AF oocytes (Figures 1b and 3b), we decided to supress SGK1 protein kinase activity in YF oocytes using the specific SGK1 inhibitor (GSK‐650394; 10 µM). SGK1 affects CDK1 activity (Hiraoka, Hosoda, Chiba, & Kishimoto, 2019), thus we validated successful SGK1 inhibition via decrease of CDK1 (Thr161) phosphorylation in YF oocytes (3 h post IBMX removal in the presence of the inhibitor) (Figure ). Subsequently, we assayed meiotic progression of YF oocytes treated with vehicle or SGK1 inhibitor.…”
Section: Resultsmentioning
confidence: 68%
“…activity (Hiraoka, Hosoda, Chiba, & Kishimoto, 2019), thus we validated successful SGK1 inhibition via decrease of CDK1 (Thr161) phosphorylation in YF oocytes (3 h post IBMX removal in the presence of the inhibitor) ( Figure S6). Subsequently, we assayed meiotic progression of YF oocytes treated with vehicle or SGK1 inhibitor.…”
Section: Perturbation Of Castor1 and Sgk1 Protein Levels/activity Lmentioning
confidence: 56%
“…HMGA2 also increases the percentages of cells in the G2/M phase by regulating CDK1 and cyclin B, which needs further exploration. 51 Overall, our results suggest that miR-4651 regulates cell proliferation and suppresses the cell cycle at the G0/G1 phase by upregulating CDK2 and cyclin D and downregulating cyclin E through inhibition of HMGA2. However, our results also showed that the roles and mechanism of HMGA2 and miR-4651 in cell cycle regulation have some differences.…”
Section: Discussionmentioning
confidence: 51%
“…Although this unknown effector of Gβγ remains to be determined, these effectors cooperatively activate serum-and glucocorticoid-regulated kinase (SGK) through two kinases, PDK1 and TORC2 ( Figure 1); starfish SGK possesses Thr312 in its activation loop and Thr479 in the hydrophobic motif (HM), which are phosphorylated by PDK1 and TORC2, respectively [22,23]. Moreover, phosphorylation of these two amino acids is required for the activation of SGK, because the inhibitors of these two protein kinases block the phosphorylation of SGK, kinase activity of SGK, and 1-MA-dependent GVBD [22,23]. Further, the antibody raised against SGK-HM completely blocks GVBD and inhibits the phosphorylation of Thr312 as well as Thr479 [22].…”
Section: Sgk-dependent Gvbdmentioning
confidence: 99%
“…These results indicate that the mutant SGK, which is phosphorylated by PDK1, induces GVBD. Moreover, the activated SGK phosphorylates Cdc25 and Myt1 [23] to activate cyclin B-Cdk1 [2] ( Figure 1). Although Akt was previously believed to be involved in the phosphorylation of Cdc25 [18] and Myt1 [24], Akt in vivo cannot activate cyclin B-Cdk1 [23].…”
Section: Sgk-dependent Gvbdmentioning
confidence: 99%